China’s information revolution : - Qiang, Christine Zhen-Wei. (World Bank, 2007)
This report presents a comprehensive overview of the information, communication and technological sector in China, and the role it has played during economic and social transformation in the past decade. It provides guidance on the kind of reforms policy makers in China may wish to consider in pursuing the country's quest for continued ICT development. It also combines local perspectives with international experiences on how issues in areas such as legal and regulatory environment, telecommunications infrastructures, and IT industry have been addressed by other countries.